Telaah Yuridis Potensi Pelanggaran Keimigrasian oleh Mahasiswa Asing di Yogyakarta: Ditinjau dari Kebijakan Pengawasan Keimigrasian - Dicky Alfian Nur Rachman; Haedarullah; Syahruramadhan; Opik Taupik Kurahman (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This research is motivated by the rampant issues regarding mental health that occur at this time. This study aims to analyze how the process of internalizing the values of mauizah hasanah as a means of Islamic therapy and students' learning motivation. The research approach used is qualitative with a literature study method, data collected from literature that discusses mauizah hasanah, Islamic psychotherapy and learning motivation using Miles and Huberman's descriptive-analytical analysis which includes data reduction, data presentation and conclusion drawing and verification. The findings of this research are that the process of internalizing value has three stages initiated by Muhaimin, namely transformation of value, transaction of value and transinternalization of value. This research shows that the internalization of the value of mauizah hasanah not only plays a role as a psychological healing based on Islamic spirituality, but also fosters students' motivation to learn based on their moral and spiritual awareness. The implications of this study include theoretical enrichment for Islamic psychology and practical recommendations for Islamic educators and counselors to internalize the values of mauizah hasanah into the context of therapy or learning. Further research is suggested to test the application of these mauizah hasanah values empirically through direct practice or education in schools